A SWOT analysis of parent-mediated intervention for children with autism spectrum disorder: Oman as a Regional Model. (3rd September 2022) - Idris, Ahmed B.; Abdulrahim, Reem; Al-Mamari, Watfa; Shih, Andy; Kantaris, Marios
Abstract : The prevalence of autism in the Arabian Gulf region is on the rise leading to overstretching of the pre-existing intervention services. The World Health Organization Caregiver Skills Training Program is a novel renovation being studied around the globe to overcome the scarcity of resources, improve autistic children's outcome and empower parents with comparable results to therapist-based models. Recently, Oman achieved great success in advocating for autism and initiated the first screening program for autism in the region. This review aims to use a Strength, Weakness, Opportunities and Threats (SWOT) analysis matrix to investigate the potential for using a parent-mediated intervention program as a supplementary approach to the currently used therapist-based intervention model in the country as an example for Gulf region.